Chemical constituents from Cynanchum paniculatum (Bunge) Kitag. (August 2015) - Niu, Ya-Le; Chen, Xi; Wu, Yi; Jiang, Hai-Qiang; Zhang, Xue-Lan; Li, En-Tao; Li, You-Ying; Zhou, Hong-Lei; Liu, Jia-Guo; Wang, De-Yun
Abstract: Twenty-nine compounds, including five acetophenone derivatives (1–5 ), three phenanthroindolizidine alkaloids (12–14 ), seven pentacyclic triterpenoids (15–21 ) and five C21 steroidal sapogenins (22–26 ), were isolated from the root of Cynanchum paniculatum (Bunge) Kitag. Their structures were determined by spectroscopic methods and comparison with reported data. Moreover, the chemotaxonomic relationships were also discussed. As a result, acetophenone derivatives, pentacyclic triterpenoids and C21 pregnane sapogenins can be recognized as chemotaxonomic markers for Cynanchum genus, and C. paniculatum has close relationships with some species of genus Cynanchum . Highlights: We studied the isolation of Cynanchum paniculatum (Bunge) Kitag and obtained twenty-nine compounds. The structures of these compounds were elucidated by spectroscopic methods. Five compounds were firstly reported from Asclepiadaceae family. Compounds7, 15–17, 19, 20 and 27 were obtained from C. paniculatum firstly for the first time. The isolated constituents exhibited the relationships between C. paniculatum and some other plants of Cynanchum genus.